2012
DOI: 10.1186/1752-1947-6-210
|View full text |Cite
|
Sign up to set email alerts
|

Visceral larva migrans associated with earthworm and gecko ingestion: a case report

Abstract: IntroductionVisceral larva migrans is a syndrome caused by an infection with larval helminths, which may result in partial or general pathological changes in host tissues. Due to the difficulty in finding the causative parasites, the diagnosis of visceral larva migrans is generally based on compatible clinical signs, epidemic history, marked eosinophilia and pathological examination, especially positive serological test results and the disappearance of symptoms after specific treatment.Case presentationWe repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The characteristic sonographic features of worms in the bile duct are the presence in the gallbladder of a single, long, linear or curved echogenic structure without acoustic shadowing, looking like an anechogenic tube, and characteristic movement of these long echogenic structures within the bile duct. Other features are less specific or are an expression of the complications and consist of gallbladder distention, edema of the gallbladder wall, sludge within the gallbladder, a coiled echogenic structure within the gallbladder, multiple liver abscesses, and edematous pancreatitis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic sonographic features of worms in the bile duct are the presence in the gallbladder of a single, long, linear or curved echogenic structure without acoustic shadowing, looking like an anechogenic tube, and characteristic movement of these long echogenic structures within the bile duct. Other features are less specific or are an expression of the complications and consist of gallbladder distention, edema of the gallbladder wall, sludge within the gallbladder, a coiled echogenic structure within the gallbladder, multiple liver abscesses, and edematous pancreatitis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that albendazole in the dose of 400 mg/day in three repeated cycles (initial two cycles for 14 days and third cycle for a week) for hepatic VLM is effective as treatment. [ 25 ] The laboratory markers used for monitoring the treatment efficacy included white blood cell, eosinophil counts, as well as liver transaminase enzymes. [ 25 ] They added a fourth course of praziquantel at a dose of 120 mg/kg for a short period of 3 days for the final normalization of the laboratory markers.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] The laboratory markers used for monitoring the treatment efficacy included white blood cell, eosinophil counts, as well as liver transaminase enzymes. [ 25 ] They added a fourth course of praziquantel at a dose of 120 mg/kg for a short period of 3 days for the final normalization of the laboratory markers. The role of high dose albendazole therapy has also been described by some authors.…”
Section: Discussionmentioning
confidence: 99%
“…These infections are highest in communities with low hygienic condition but also take place in developed countries in susceptible persons (3). Infections by earthworms an uncommon parasitic worms that infect humans have been reported rarely (4). This article reports on a rare case of infection with a kind of earthworm diagnosed by optical microscopy in an Iranian 21-months-old female from Karaj.…”
Section: Dear Editor-in-chiefmentioning
confidence: 99%